Pilot Study of Pollution Characteristics and Ecological Risk of Disinfection Byproducts in Natural Waters in Hong Kong. (13th September 2022) - Liu, Jing; Hu, Li‐Xin; Deng, Wen‐Jing; Ying, Guang‐Guo; Hong, Huachang; Tsang, Eric P. K.; Barceló, Damià
Abstract: Increased disinfection efforts in various parts of China, including Hong Kong, to prevent the spread of the novel coronavirus may lead to elevated concentrations of disinfectants in domestic sewage and surface runoff in Hong Kong, generating large quantities of toxic disinfection byproducts. Our study investigated the presence and distribution of four trihalomethanes (THMs), six haloacetic acids (HAAs), and eight nitrosamines (NAMs) in rivers and seawater in Hong Kong. The concentrations of THMs (mean concentration: 1.6 µg/L [seawater], 3.0 µg/L [river water]), HAAs (mean concentration: 1.4 µg/L [seawater], 1.9 µg/L [river water]), and NAMs (mean concentration: 4.4 ng/L [seawater], 5.6 ng/L [river water]) did not significantly differ between river water and seawater. The total disinfection byproduct content in river water in Hong Kong was similar to that in Wuhan and Beijing (People's Republic of China), and the total THM concentration in seawater was significantly higher than that before the COVID‐19 pandemic. Among the regulated disinfection byproducts, none of the surface water samples exceeded the maximum index values for THM4 (80 μg/L), HAA5 (60 μg/L), and nitrosodimethylamine (100 ng/L) in drinking water. Among the disinfection byproducts detected, bromoform in rivers and seawater poses the highest risk to aquatic organisms, which warrants attention and mitigation efforts. Environ Toxicol Chem 2022;41:2613–2621. © 2022 SETAC